Two-criteria optimisation problem for ventral hernia repair. Issue 7 (19th May 2017) - Szymczak, Czesław; Lubowiecka, Izabela; Szepietowska, Katarzyna; Tomaszewska, Agnieszka
Abstract: Two-criteria optimisation problem related to laparoscopic ventral hernia repair is formulated in this paper. An optimal implant from a given set and its orientation is sought. The implant is subjected to kinematic extortions due to a patient's body movement and intra-abdominal pressure. The first criterion of the optimisation problem deals with the reaction force in the implant fastener, while the deflection of the implant constitutes the second criterion. A two-stage optimization procedure is proposed and the optimal solution is determined with the aid of minimization of an additional objective function. Numerical examples for typical locations of hernia are provided.